Pediatric traumatic emergencies - Dietrich, Ann M. (New York, NY : Oxford University Press, 2020)
'Pediatric Traumatic Emergencies' uses a case-based approach to cover common and important topics in the examination, investigation, and management of injured children. Each chapter provides a discussion of the diagnosis, key points to remember, and selected references for further reading.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 14, 2020).
Keywords: Pediatric emergencies; Children -- Wounds and injuries -- Treatment